2014
DOI: 10.5296/rbm.v1i2.5500
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility (CSR) Practices and Stakeholders Expectations: The Nigerian Perspectives

Abstract: Using Carroll's (1991) Corporate Social Responsibility (CSR) model, the study examines business CSR practices and stakeholders' expectations in Nigeria. Carroll's (1991) CSR model states that four kinds of social responsibilities constitute total CSR: economic, legal, ethical, and philanthropic. Both primary (survey) and secondary (the literature) data are used for the study. There are several stakeholders in business; but, for the purpose of the study employees, customers, shareholders, and local communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…Many international studies have found empirical evidence that the cost of proprietary is one of the most important factors when a company discloses sustainability information. Fadun (2014) suggested that the proprietary cost was considered as an important limitation of information disclosure, a competitive disadvantage affecting the decision to provide private information. When voluntarily disclosure information on sustainable development, it is possible that the company will incur costs due to declining future cash flow from the disclosure of this information, but it is likely to increase later in different ways.…”
Section: Proprietary Cost Theorymentioning
confidence: 99%
“…Many international studies have found empirical evidence that the cost of proprietary is one of the most important factors when a company discloses sustainability information. Fadun (2014) suggested that the proprietary cost was considered as an important limitation of information disclosure, a competitive disadvantage affecting the decision to provide private information. When voluntarily disclosure information on sustainable development, it is possible that the company will incur costs due to declining future cash flow from the disclosure of this information, but it is likely to increase later in different ways.…”
Section: Proprietary Cost Theorymentioning
confidence: 99%
“…Carroll & Buchholtz (2011) and Deegan (2002) stated that companies have a responsibility to shareholders, society and the environment. (Fadun, 2014) Economic responsibility refers to improving shareholders by increasing profit per share, competitiveness, and efficiency (Carroll, 2016). To adhere to legal responsibility, companies should maintain business stability by complying with applicable regulations, constitution, and laws (De Schutter, 2008;Phillips, Freeman, & Wicks, 2003).…”
Section: Social Responsibilitymentioning
confidence: 99%
“…employees, customers, suppliers, host communities, shareholders and the society at large) in a business is a useful way of developing socially responsible behaviour by managers (Maignan, Ferrell, 2004;Agudelo et al, 2019). The stakeholder theory therefore takes into account the need to satisfy those interested parties capable of influencing firm performance and outcomes (Abiola, 2014;Fadun, 2014;Nasieku et al, 2014). A socially responsible corporate firms seen as one in which obligations to stakeholders figure prominently in the decision-making of managers (Clarkson, 1995;Park, Ha, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%